Impact of Smartphone Application Education on Stress in Type 2 Diabetes Mellitus Patients - Bagus Santosa, Winanda Rizki; Nisha Nambiar; Erlina Abdullah (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Lack of knowledge about managing health and the duration of the disease causes stress in Diabetes Mellitus (DM) patients. Uncertainty about their future health and the ongoing burden of disease can worsen the mental health of type 2 diabetes mellitus (T2DM) patients. Smartphone application education can be a solution for T2DM patients in reducing stress regarding their health condition. This study aims to determine the impact of smartphone application education on stress in type 2 diabetes mellitus patients. Methods: The design in this research is a pre-test and post-test control group design. The research was conducted in the period October 2023 – January 2024. Respondents in this study were T2DM patients. The locations of this research were nine Public Health Centers in Kediri City, Indonesia. The sample in this study was 131 respondents. Results: The results of the research showed that the stress score for T2DM sufferers in the pre-test was 41.34, after three months of smartphone application education, post-test the mean stress decreased was 4.31, and the p-value 0.000. There is a mean difference October – November was 13.50, November – December was 10.77, December – January was 12.76 and the P-Value was 0.008. Conclusion: There was a decrease in stress during the periods of October, November, December, and January after being given smartphone application education. Smartphone applications are effective in reducing stress in T2DM patients.